Melacak Pemikiran Masyarakat sebagai Jiwa Agama - Purwanto, Purwanto (Program Studi Studi Agama-Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2011)
Being understood of human life included in the way of thinking and behavior basically need to rely on three elemental points or social dimensions of society; social structure, social interaction and social institutions. The whole activities of human life, morality and laws, Jobs and relaxation, family and personality, knowledge, art and everything named as religion come and pass through those social dimensions.  Religion is considered as the essential value that controls behavior of each individual of society. Functionalism says that superstructure of ideology is the main standard which affects the framework in social structure and infra-structure. To understand religiosity of a certain society depends on how we deeply know the life style of them. Later, it also depends on their social structure. In this context religion is commonly seen as the agent of moral socialization. Religion becomes the principal values that organize the attitude of society. To perform their activities, religious people will attempt to unify three elements of beliefs, symbols and rituals. This article tries to describe how the role of religion plays on the level of social through which elemental aspects of human life following and joining in shaping the condition of human life, behavior, ethic, culture, tradition and etcetera.